Effects of meal composition on postprandial incretin, glucose and insulin responses after surgical and medical weight loss. (7th December 2015) - Lee, C. J.; Brown, T. T.; Cheskin, L. J.; Choi, P.; Moran, T. H.; Peterson, L.; Matuk, R.; Steele, K. E.
Summary: Background: Meal tolerance tests are frequently used to study dynamic incretin and insulin responses in the postprandial state; however, the optimal meal that is best tolerated and suited for hormonal response following surgical and medical weight loss has yet to be determined. Objective: To evaluate the tolerability and effectiveness of different test meals in inducing detectable changes in markers of glucose metabolism in individuals who have undergone a weight loss intervention. Methods: Six individuals who underwent surgical or medical weight loss (two Roux‐en‐Y gastric bypass, two sleeve gastrectomy and two medical weight loss) each completed three meal tolerance tests using liquid‐mixed, solid‐mixed and high‐fat test meals. The tolerability of each test meal, as determined by the total amount consumed and palatability, as well as fasting and meal‐stimulated glucagon‐like peptide, glucose‐dependent insulinotropic polypeptide, insulin and glucose were measured. Results: Among the six individuals, the liquid‐mixed meal was better and more uniformly tolerated with a median meal completion rate of 99%. Among the four bariatric surgical patients, liquid‐mixed meal stimulated on average a higher glucagon‐like peptide (percent difference: 83.7, 89), insulin secretion (percent difference: 155.1, 158.7) and glucose‐dependent insulinotropic polypeptide (percent difference: 113.5, 34.3) compared with solid‐mixed and high‐fat meals. Conclusions: The liquid‐mixed meal was better tolerated with higher incretin and insulin response compared with the high‐fat and solid‐mixed meals and is best suited for the evaluation of stimulated glucose homeostasis.